2022
DOI: 10.1016/j.heliyon.2021.e08653
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of diabetes risk in urban and rural areas in Colombia

Abstract: Background: Nutritional habits low in fruits and vegetables and sedentary lifestyle are associated with a higher risk of developing Type 2 Diabetes (T2D). However, it is important to assess differences between urban and rural areas. This study aimed to analyze the associations between the risk of developing T2D and setting in the Colombian north coast in 2017. Methods: This cross-sectional study included 1,005 subjects. Data was collected by interviewing self-identified members of an urban community and a rura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…This is supported by the results of research on predicting diabetes risk in people living in urban and rural areas in Columbia. The study found that people who live in urban areas are 1.9 times more at risk of suffering from diabetes than people who live in rural areas (Molina, R.T., Garcia, A.L.R., Vergora, T.A., Garcia, V.A.F., Guiterrez, V.R., Lozano, K.F., & Barengo, 2022).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This is supported by the results of research on predicting diabetes risk in people living in urban and rural areas in Columbia. The study found that people who live in urban areas are 1.9 times more at risk of suffering from diabetes than people who live in rural areas (Molina, R.T., Garcia, A.L.R., Vergora, T.A., Garcia, V.A.F., Guiterrez, V.R., Lozano, K.F., & Barengo, 2022).…”
Section: Discussionmentioning
confidence: 86%
“…Likewise, the results of a study in Columbia predict that the risk of getting T2DM in cities is higher than in rural areas (Molina, R.T., Garcia, A.L.R., Vergora, T.A., Garcia, V.A.F., Guiterrez, V.R., Lozano, K.F., & Barengo, 2022). Whereas in Nigeria, in general, metabolic syndrome diseases such as T2DM, according to the IDF report, the difference in cities is more significant than in rural areas by 21.7% (Adejumo.…”
Section: Introductionmentioning
confidence: 99%
“…There are many possible causes for the increase in the number of cases of diabetes including urbanization, a swift and social alteration, lack of regular exercise regimen, malnutrition, and obesity. [6][7][8][9] Diabetes has been proven to be reduced by eating a low-fat, highfiber diet. 7 As a result, eating fruits and vegetables daily helps to reduce the chance of developing diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Diabetes has been proven to be reduced by eating a low-fat, highfiber diet. 7 As a result, eating fruits and vegetables daily helps to reduce the chance of developing diabetes. People with diabetes who want to live a normal life and their family members need to know a lot about their illness.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 77.5% of the study population in Abuja do not consume vegetables or fruits daily32 , while Alebiosu et al26 observed that only 27.8% of the study population in Ogun state consume vegetables, fruit or berries every day. Other studies, such as that of Molina et al50 conducted on a Colombian population, found that 26.9% of the urban area residents consume fruits and vegetables regularly with an average FINDRISC score…”
mentioning
confidence: 82%